The American Retail Value Proposition : Crafting Unique Experiences at Compelling Prices - Murray, Kyle B. (Kyle Bayne), 1973- (Book collections on Project MUSE., 2016)
Whether you are an aspiring merchant or an industry veteran, this book's strategic framework will help you build a solid foundation for your business in today's ever-evolving retail marketplace.